Structural insight of a photosystem I-CpcL-phycobilisome supercomplex from a cyanobacterium Anabaena sp. PCC 7120 - Zhiyuan Mao; Zhenhua Li; Xingyue Li; Liangliang Shen; Tingyun Kuang; Wenda Wang; Jian-Ren Shen; Guangye Han (Proceedings of the National Academy of Sciences, 2026)
Phycobilisomes (PBSs) are supramolecular pigment–protein complexes composed of phycobiliproteins and linker proteins, serving as the major light-harvesting complexes that capture and transfer light energy to photosystem II (PSII) and photosystem I (PSI) in cyanobacteria and eukaryotic red algae. In cyanobacteria, a rod-type PBS that does not have a core is specifically connected to PSI by a linker protein CpcL to form a PSI-CpcL-PBS supercomplex. However, the mechanism of CpcL-PBS association to PSI remains unclear. Here, we report the cryoelectron microscopic structures of PSI-CpcL-PBS at 2.98 Å and CpcL-PBS at 2.93 Å resolution from a cyanobacterium Anabaena sp. PCC 7120, respectively. CpcL-PBS is located on the stromal side of a PSI tetramer and exhibits a structure of three-layered PBS consisting of four linkers (CpcL, CpcC1, CpcC2, PecC) and 18 pairs of phycocyanin αβ monomers. The C-terminal transmembrane helix of CpcL inserts to the membrane and interacts with PsaA, PsaB, and PsaM of PSI at an interface I between two PSI monomers, enabling the formation of the PSI-CpcL-PBS supercomplex. The exact structure of protein subunits and arrangement of bilin and chlorophyll pigments are revealed, which provide a structural basis for the assembly of PSI-CpcL-PBS and possible excitation energy transfer pathways from antennas to PSI within this supercomplex, shedding light on the organization and attachment of CpcL-PBS in cyanobacterial thylakoids.